Ring-Pins combined with cable cerclage for the fixation of displaced inferior patellar pole fractures - Jian, Zhen; Jia, Jianbo; Zeng, Langqing; Li, Dejian; Zhang, Xu; Zhou, Jianhua; Yi, Chengqing; Yu, Baoqing; Ao, Rongguang (Frontiers in Surgery, 2023)
Objective The purpose of this retrospective study was to present the functional outcomes and complication rates of ring-pins with cable cerclage for treating the inferior pole of the patella fracture. Method A retrospective study that reviewed consecutive patients of displaced inferior patellar pole fractures (AO/OTA 34-A1) operated with ring-pin tension band using cable cerclage between October 2015 and October 2017 was performed. The duration of surgery, motion range of the knee, function outcomes, and complications were recorded. Results The average follow-up of 31 patients was 21 months. The mean operation time was 50 minutes. All fractures healed at a mean of 8 weeks. There was no infection, no withdrawing of ring-pings, no implant breakage and no loss of fracture reduction. At final follow-up, no patients complained of irritation of implant. The average range of motion was 120°. The mean Bostman score at last follow-up was 29.0 points and graded excellent in 28 patients, good in 3 patients. Conclusions Ring-Pin combined with cable cerclage for the treatment of displaced inferior patellar pole fractures is simple, and the postoperative internal fixation-related complication rate is low. It is a good choice for the treatment for displaced inferior patellar pole fractures.